2020
DOI: 10.1002/cnma.202000056
|View full text |Cite
|
Sign up to set email alerts
|

2D Metal‐Organic Framework Derived Co3O4 for the Oxygen Evolution Reaction and High‐Performance Lithium‐Ion Batteries

Abstract: Recently, MOF-derived (metal-organic framework) 2D materials, due to the special structure of the MOF inherited, have become a potential candidate for application in energy storage and conversion. In this work, a new 2D layered CoÀ MOF was synthesized as the precursor for fabricating Napoleon-like Co 3 O 4 (NLÀ Co 3 O 4). The monolayer thickness of NLÀ Co 3 O 4 is approximately 70 nm. The unique structure of layered porous of NLÀ Co 3 O 4 derived from CoÀ MOF plays an important role in improving electrochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…MOFs have been extensively investigated for gas storage, 23 separation, 24 purification, 25,26 catalysis, 27–31 drug delivery, 32–34 sensing, 35 thin‐film systems, 36,37 and other fields due to the unique merits of crystalline porous structure, highly dispersed metal components, and tunable pore size 38–40 . As electrode materials for energy storage devices, MOFs are mainly divided into two categories: pristine MOFs materials 41–43 and their derived nanostructures (such as nanoporous carbons and metal oxides) 44–46 . In recent years, there have been a great number of research on the pyrolysis of MOFs as precursors to obtain nanoscale metals or metal compounds and nanostructured carbon materials, and most of the materials derived from MOFs have better electrochemical properties than traditional materials 47–50 .…”
Section: Introductionmentioning
confidence: 99%
“…MOFs have been extensively investigated for gas storage, 23 separation, 24 purification, 25,26 catalysis, 27–31 drug delivery, 32–34 sensing, 35 thin‐film systems, 36,37 and other fields due to the unique merits of crystalline porous structure, highly dispersed metal components, and tunable pore size 38–40 . As electrode materials for energy storage devices, MOFs are mainly divided into two categories: pristine MOFs materials 41–43 and their derived nanostructures (such as nanoporous carbons and metal oxides) 44–46 . In recent years, there have been a great number of research on the pyrolysis of MOFs as precursors to obtain nanoscale metals or metal compounds and nanostructured carbon materials, and most of the materials derived from MOFs have better electrochemical properties than traditional materials 47–50 .…”
Section: Introductionmentioning
confidence: 99%
“…8−11 On the one hand, a large number of researchers have studied the relationship between the MOS sensing materials' micro-structure and gas sensing performance and pointed out that the preparation of mesoporous and hollow hierarchicalstructured MOS is an effective measure to enhance VOC sensing performance owing to its efficient sensing active sites and gas adsorption/diffusion. 12−15 Recently, with the deepening of research, the mesoporous metal oxide semiconductors derived from metal−organic framework (MOF) have been successfully and widely used in various fields, for instance, supercapacitors, 16,17 lithium-ion batteries, 18,19 catalysts, 20,21 and gas sensors, 22−28 due to their advantages of larger specific surface area (SSA), larger pore volume, abundant mesoporous structure, and tunable morphology. Meanwhile, recent studies have shown that the cation-exchange approach can be applied for the fabrication of bimetallic metal−organic frameworkderived metal oxide composites composed of two dissimilar semiconducting materials, which is an emerging preparation 30 On the other hand, in addition to the regulation of microstructure of MOS, many studies have shown that the selectivity and other important sensing parameters of MOS gas sensor can be further improved through constructing metal oxide composites, due to the formation of the heterojunction accompanied with the charge transfer/separation, increased interfacial potential barrier energy.…”
mentioning
confidence: 99%
“…In the past few decades, metal oxide semiconductor (MOS) gas sensors have attracted much attention, particularly in VOC detection, due to their simple preparation method, easy miniaturization, cost effectiveness, and high sensitivity. On the one hand, a large number of researchers have studied the relationship between the MOS sensing materials’ microstructure and gas sensing performance and pointed out that the preparation of mesoporous and hollow hierarchical-structured MOS is an effective measure to enhance VOC sensing performance owing to its efficient sensing active sites and gas adsorption/diffusion. Recently, with the deepening of research, the mesoporous metal oxide semiconductors derived from metal–organic framework (MOF) have been successfully and widely used in various fields, for instance, supercapacitors, , lithium-ion batteries, , catalysts, , and gas sensors, due to their advantages of larger specific surface area (SSA), larger pore volume, abundant mesoporous structure, and tunable morphology. Meanwhile, recent studies have shown that the cation-exchange approach can be applied for the fabrication of bimetallic metal–organic framework-derived metal oxide composites composed of two dissimilar semiconducting materials, which is an emerging preparation concept for precisely controlling the proportion of each component in composites because the bimetallic metal–organic framework can serve as the self-sacrificial template or precursor to produce the hierarchically porous nanoarchitecture.…”
mentioning
confidence: 99%